Spectroscopic ellipsometry as an optical probe of strain evolution in ferroelectric thin films - Lei,DY; Kéna-Cohen,S; Zou,B; Petrov,PK; Sonnefraud,Y; Breeze,J; Maier,SA; Alford,NM (Opt. Express, 2012)
Heteroepitaxial strain in ferroelectric thin films is known to have a significant impact on both their low and high frequency dielectric properties. In this paper, we use ex-situ spectroscopic ellipsometry to study the strain evolution with film thickness, and strain relaxation in ferroelectric Ba0.5Sr0.5TiO3 epitaxial films grown on single crystal substrates. For films grown on MgO substrates, a critical thickness for strain relaxation is observed. In addition, studies of Ba0.5Sr0.5TiO3 films grown on different single crystal substrates reveal that the strain relaxation rate can be inferred from changes in the optical properties. Using this information, we show that the optical constants of Ba0.5Sr0.5TiO3 can be readily tuned via strain engineering.